The impact of income statement indicators in evaluating earnings management - Naser Abbas Al-Daami, Ahmed (Iraqi Journal for Administrative Sciences, 2024)
The income statement represents one of the four basic statements stipulated in Standard (IAS1) (presentation of financial statements), through which the ability of the economic unit to generate revenues and fulfill its obligations to others and the efficiency of its operational operations in achieving profits can be determined. Hence the idea of research came to shed light on the indicators of this statement and demonstrate their impact on evaluating profit management through the results of the analysis using profitability indicators. The Modern Sewing Company was chosen as a sample for the research to demonstrate this effect by calculating the company’s profitability ratios during the years (2018-2020). The research reached a set of conclusions, the most important of which are: The income statement indicators provide a chronological sequence of profits from the beginning of revenue generation until the amount of net profit and the changes that occur to it.